Nasvac: A Novel Warrior in a Strategic Battle for the Global South - Rubido, Julio Cesar Aguilar; Al Mahtab, Mamun; Akbar, Sheikh Mohammad Fazle (British Journal of Healthcare and Medical Research, 2025)
Chronic hepatitis B virus (HBV) infection remains one of the most significant global health challenges, with approximately 1 million deaths annually due to complications such as cirrhosis, liver failure, and hepatocellular carcinoma (HCC). Despite advances in the field of therapies, achieving a functional cure-defined as sustained loss of hepatitis B surface antigen (HBsAg) and undetectable HBV DNA-remains elusive. Current treatments, including nucleos(t)ide analogs (NUCs) and pegylated interferon (PegIFN), have limitations in efficacy, safety, and effectiveness, particularly in low- and middle-income countries where the burden of HBV is highest. In this context, therapeutic vaccination emerges as a promising strategy, leveraging the immune system to mount a coordinated and sustained attack against HBV. Nasvac, a novel therapeutic vaccine that will enter in real-life studies after a successful registration and post-marketing phase IV studies, represents a paradigm shift in the fight against CHB, offering a multi-pronged approach that activates both innate and adaptive immunity. This article revisit the current situation in the Global South in respect of Chronic Hepatitis B and explores the rationale and mechanisms of Nasvac, compares it to current therapies, and draws parallels to military strategy, ultimately calling for a global focus on the "war against the pathogen".